Manajemen Peserta Didik - Astuti Astuti (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
This article discusses student management. In realizing effective governance of educational institutions, all components in it must be managed properly, including students. Student management is the whole process of activities that are planned and endeavored intentionally as well as continuous guidance for all students so that they can participate in the teaching and learning process effectively and efficiently starting from the admission of students to the discharge of students from a school. In management, participants must be goal-oriented, adhering to the principles of student management, student management approaches, student management functions, and structuring the entire scope of student management.